Clinical Significance of Procalcitonin, C-Reactive Protein, and Interleukin-6 in Helping Guide the Antibiotic Use for Patients with Acute Exacerbations of Chronic Obstructive Pulmonary Disease. (15th March 2021) - Song, Wen; Wang, Yue; Tian, Fengming; Ge, Liang; Shang, Xiaoqian; Zeng, Qiang; Feng, Ning; Fan, Jiahui; Wang, Jing; Ma, Xiumin
Abstract : Background . Currently, standards of antibiotic use in acute exacerbations of chronic obstructive pulmonary disease (AECOPD) patients are controversial. Objective . The aim of the present study was to analyze the value of procalcitonin (PCT), C-reactive protein (CRP), and interleukin-6 (IL-6) levels to guide the antibiotic treatment of AECOPD patients. Methods. A total of 371 patients with COPD or AECOPD were included in the study. Clinical and laboratory data were obtained at admission, 325 AECOPD patients and 46 sCOPD patients treated with antibiotics. The receiver operating curve (ROC) was used to evaluate the relationship between CRP, PCT, and IL-6. Results. This study included medical record/case control 1, the COPD group (n = 46 ) and the AECOPD group (n = 325 ), and medical record control 2, the nonchanged antibiotic group (n = 203 ) and the changed antibiotic group (n = 61 ). In case 1, CRP, PCT, and IL-6 levels in the AECOPD group were higher than that in the control group (P < 0.05 ), while the result of ROC showed that IL-6 had higher AUC values (0.773) and higher sensitivity (71.7%) than other indicators. The specificity of PCT (93.5%) is higher than other indicators. In case 2, ROC curve results showed that the AUC value of IL-6 (0.771) was slightly higher than PCT and CRP. The sensitivity (85.2%) and specificity (65.5%) of CRP were higher than other indicators. Conclusions. IL-6 and PCT were elevated in AECOPD patients, resulting in a higher diagnostic value for AECOPD. CRP had a higher diagnostic value for antibiotic use in AECOPD patients.